Electrochemical investigation of the dimeric oxo-bridged ruthenium complex in aqueous solution and its incorporation within a cation-exchange polymeric film on the electrode surface for electrocatalytic activity of hydrogen peroxide oxidation - Teixeira, Marcos F. S. [UNESP]; Cincotto, Fernando H. [UNESP]; Raymundo-Pereira, Paulo A. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Electrochemical behavior of oxo-bridged dinuclear ruthenium(III) complex ([(bpy)2(H(2)O)Ru(III)-O-Ru(III)(H(2)O)(bpy)2](4+)) has been studied in aqueous solution (KCl 0.5 mol L(-1)) by both cyclic and rotating disk electrode (ROE) voltammetry in order to identify and elucidate the reaction mechanism. Modified electrode containing the oxo-bridged ruthenium complex incorporated into a cation-exchange polymeric film deposited onto platinum electrode surface was studied. Cyclic voltammetry at the modified electrode in KCl solution showed a single-electron reduction/oxidation of the couple Ru(III)-O-Ru(III)/Ru(III)-O-Ru(IV). The modified electrode exhibited electrocatalytic property toward hydrogen peroxide oxidation in KCl solution with a decrease of the overpotential of 340 mV compared with the platinum electrode. The Tafel plot analyses have been used to elucidate the kinetics and mechanism of the hydrogen peroxide oxidation. The first at low overpotential region there is no significant change in the Tafel slope (similar to 0.130 V dec(-1)) with varying peroxide concentration. The second region at higher overpotential the slope values (0.91-0.47V dec(-1)) were depended on the peroxide concentration. The apparent reaction order for H(2)O(2) varies from 0.16 to 0.50 in function of the applied potential. The apparent reaction order (at constant potential) with respect to H. concentration of 10(-5) to 10(-1) mol L(-1) was 0.25. A plot of the anodic current vs. the H(2)O(2) concentration for chronoamperometry (potential fixed = +0.61 V) at the modified electrode was linear in the 1.0 x 10(-5) to 2.5 x 10(-4) mol L(-1) concentration range. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Polynuclear-ruthenium; Electrochemical behavior; H(2)O(2) oxidation; Tafel slope